Meeting on the decline of the urban House Sparrow "Passer domesticus": Newcastele 2011 (10-11 March) - Laet, Jenny De; Weir, Jacqueline; Peach, Will (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The Working Group on Urban Sparrows is investigating the decline of urban sparrows "Passer", in urban and suburban habitats. At the second meeting in 2009 (De Laet et al 2009) it was decided to define a standardized census procedure that would enable meaningful comparisons of the House Sparrow "P. domesticus" breeding density in urban/suburban habitats throughout this species` range.
Keywords: wróblowe; ornitologia